2012
DOI: 10.1093/ejcts/ezs363
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and mid-term features of left ventricular reconstruction procedures on left ventricular volume, geometry, function and mitral regurgitation

Abstract: Despite the more spherical LV change, LVR led to a significant volume reduction (45%), still maintaining its physiological shape that confirmed an improved LV function and better long-term results. The Dor procedure could significantly reduce the larger LV volume without losing the end-systolic elliptical shape and mitral valvular competence like other techniques without the Fontan stitch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
2
0
5
Order By: Relevance
“…Имеются данные, что ХРЛЖ, усиливая систолическую функцию ЛЖ, также способна ухудшать диастолические свойства ЛЖ, что приводит к повышению давления наполнения ЛЖ и увеличению постнагрузки ПЖ [59]. Более того, изменение геометрии ЛЖ после ХРЛЖ влияет на положение и функцию межжелудочковой перегородки, которая, в свою очередь, влияет на геометрию и функцию ПЖ [60]. Сокращение межжелудочковой перегородки способно изменять функцию и сердечный выброс ПЖ, несмотря на отсутствие нарушений со стороны свободной стенки ПЖ.…”
Section: дисфункция правого желудочка при икмпunclassified
See 1 more Smart Citation
“…Имеются данные, что ХРЛЖ, усиливая систолическую функцию ЛЖ, также способна ухудшать диастолические свойства ЛЖ, что приводит к повышению давления наполнения ЛЖ и увеличению постнагрузки ПЖ [59]. Более того, изменение геометрии ЛЖ после ХРЛЖ влияет на положение и функцию межжелудочковой перегородки, которая, в свою очередь, влияет на геометрию и функцию ПЖ [60]. Сокращение межжелудочковой перегородки способно изменять функцию и сердечный выброс ПЖ, несмотря на отсутствие нарушений со стороны свободной стенки ПЖ.…”
Section: дисфункция правого желудочка при икмпunclassified
“…Вклад сокращения перегородки в систолическую функцию ПЖ колеблется от 24 % в нормальном ПЖ до 35 % в условиях патологии. Поэтому предоперационная оценка функции ПЖ и массы ПЖ представляется важной переменной, которую следует учитывать при отборе пациента для ХРЛЖ [60].…”
Section: дисфункция правого желудочка при икмпunclassified
“…4,5) Additionally, it was demonstrated that concomitant functional MR is one of the risk factors for long-term survival in ischemic heart disease. 6,7) Thus, ICM with functional MR is the most critical combination and the definitive treatment is heart transplantation. 8) However, heart transplantation would not be performed in all indicated patients due to the shortage of donor organs.…”
Section: Introductionmentioning
confidence: 99%
“…Este último periodo es el que incluye el infarto agudo de miocardio. (3,4,5,22,23,140,165,203,204,205) El infarto agudo de miocardio (3,4,5,140) se define como el daño celular isquémico irreversible que conduce a la necrosis de los miocitos.…”
Section: Enfermedad Coronaria: Definiciones Y Clasificación 121 Deunclassified
“…El infarto agudo de miocardio (3,4,5,22,23,140,203,204,205) se define como la muerte de células miocárdicas, de etiología isquémica, que condiciona un menor número de células útiles para la contracción. Clásicamente pág.…”
unclassified